Improving the Quality of Education Through the Implementation of Madrasah Culture Based on the 2020 Education Unit Accreditation Instrument (IASP) in the Perspective of Strategic Management at MAN 1 Bandung - Miftahul Anwar; Mulyawan Safwandy Nugraha (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to improve the quality of education at MAN 1 Bandung through the implementation of madrasah culture based on the 2020 Education Unit Accreditation Instrument (IASP). The approach used is strategic management, which allows for the identification, analysis, and implementation of effective strategies to achieve educational goals. This study examines the extent to which the existing madrasah culture can support the improvement of educational quality, as well as how strategic management can be applied to maximize accreditation results. The findings indicate that the implementation of madrasah culture in accordance with IASP 2020, combined with appropriate strategic management, can significantly enhance the quality of education at MAN 1 Bandung.